2009
DOI: 10.1007/s12666-009-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Dried leaves — Novel reductant for acid leaching of manganese ore

Abstract: In the present investigation results on the use of dried leaves as a reductant for manganese ore leaching is reported. A complete flow-sheet consisting of steps such as reductive acid leaching, enrichment of leach solution by recycling, iron removal and crystallization has been developed for the preparation of manganese sulphate monohydrate from manganese ore of Gujarat Mineral Development Corporation (GMDC), Ahmedabad, India. During leaching effects of pulp density, amount of acid, temperature, particle size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Hariprasad et al . reported that the dried leaves as a reductant could enrich 90 g/L Mn in the leach liquor. According to Cheng et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hariprasad et al . reported that the dried leaves as a reductant could enrich 90 g/L Mn in the leach liquor. According to Cheng et al .…”
Section: Introductionmentioning
confidence: 99%
“…At present, reports of the feasibilities of hazardous organics for the reduction of manganese peroxide increase. Hariprasad et al [7] reported that the dried leaves as a reductant could enrich 90 g/L Mn in the leach liquor. According to Cheng et al [8] the pyrolusite ore was reduced by biomass cornstalk roasting and then sulfuric acid-leached with 90.2% recovery of manganese.…”
Section: Introductionmentioning
confidence: 99%
“…are reported for the extraction of Mn from low grade ores. Apart from these, the uses of some nonconventional reductants like saw dust, waste paper, dried leaves are also reported. Overall carbohydrates are nonhazardous and low cost reducing agents that may be used either in pure form or as industrial/agricultural wastes. , As the reductive leaching deserves a close investigation, in one of our recent works, we have made an alternative cost-effective approach through reductive leaching of marine nodules using sulfuric acid and paper cuttings as reductant …”
Section: Introductionmentioning
confidence: 99%
“…are reported for the extraction of Mn from low grade ores. Apart from these, the uses of some nonconventional reductants like saw dust, 17 waste paper, 18 dried leaves 19 are also reported. Overall carbohydrates are nonhazardous and low cost reducing agents that may be used either in pure form or as industrial/agricultural wastes.…”
Section: Introductionmentioning
confidence: 99%
“…[13] For the low-or middle-grade pyrolusite, hydrometallurgy is extensively applied in the reduction of quadrivalence manganese because of its efficiency and economy. Generally, there are three kinds of hydrometallurgical reductants: organic materials including glucose, [14][15][16] sucrose, [17] cellulose, [18] and methanol [19] ; inorganic materials including pyrite, [20] hydrogen peroxide, [21] and sulfur dioxide [22] ; biomass including molasses [23] and molasses alcohol wastewater, [24] sawdust, [25] corncob, [26] dried leaves, [27] waste tea-leaves, [28] and so on. Although there have been many reductants reported on hydrometallurgy, few C 1 organic reductants have been investigated.…”
Section: Introductionmentioning
confidence: 99%